MARKETING ANALYSIS OF CUTTED COW IN KECAMATAN KONDA AND WEST RANOMEETO DISTRICT SELATAN KONAWE - Yusuf, La Ode Muh; Sani, La Ode Arsad; Hadini, Hairil; Munadi, Laode Muh (Pascasarjana Universitas Sulawesi Tenggara, 2021)
This study aimed to analyze the marketing of beef cattle in the Sub District Konda and Ranomeeto Barat, Konawe Selatan Regency, held in October 2017. The subjects in this study were beef cattle traders and all the aspects related to the marketing of beef cattle. The research location was determined by purposive sampling. Measured variables included the characteristics of respondents, marketing agencies, marketing channels, marketing margins, costs and benefits of any marketing agencies, and marketing efficiency. Data were analyzed qualitatively and quantitatively. Results indicated that there are four marketing channels of beef cattle in the Sub District of Konda and Ranomeeto Barat, namely (1) the farmer - the end consumer, (2) the farmer - the trader - the end consumer, (3) farmer - wholesalers - the end customer, (4) the farmer - trader - wholesalers - the end consumer. The highest margin was on the marketing channel 3 as much as Rp 1,222,026/head and the lowest was in the marketing channel 2 as much as Rp 461,895/head. The highest costs were in the marketing channel 4 as much as Rp 400,000/head, and the highest profit was in the marketing channel 3 as much as Rp 1,022,026/head. The most efficient marketing channel used was the marketing channel 3, with the marketing efficiency value 2.71%.